Long-term outcomes of ossiculoplasty using bone cement - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2019)
Objective. This study aimed to evaluate the long-term results of ossiculoplasty using bone cement. Method. Forty patients (24 females and 16 males; mean age: 34.1 +/- 11.8 years; range, 9-54 years) with chronic otitis media with perforation but without cholesteatoma who had undergone incudostapedial rebridging ossiculoplasty using bone cement were evaluated retrospectively. Pre-operative and post-operative audiograms were evaluated. Bone conduction, air conduction and air-bone gaps were calculated according to international guidelines. Results. There was a mean reduction in pre-operative and post-operative air conduction (12.30 +/- 11.98 dB), and this result was significant (p = 0.0001). There was a mean reduction in pre-operative and post-operative bone conduction (4.30 +/- 6.69 dB), and this result was significant (p <0.0001). The pre-operative air-bone gap was 27.65 dB and decreased to 19.65 dB during follow-up (p = 0.0001). No adverse reactions or complications were observed. Conclusion. Bone cement is reliable for the repair of incudostapedial-joint defects.
Keywords: Bone Cement; Incus; Ossicular Replacement; OSSICULAR RECONSTRUCTION; INCUS; STAPES